Interaction networks and the use of floral resources by male orchid bees (Hymenoptera: Apidae: Euglossini) in a primary rain forests of the Chocó Region (Colombia) - Ospina-Torres, Rodulfo (2015)
Orchid bees are important keystone pollinators from the Neotropics. With the aim to study the relationships between orchid bees and their nectar and aromatic host species, we made systematic samplings of males across two conservation areas in the biogeographic Chocó Region of Colombia. We used chemical baits to collect 352 male bees during five months. The pollen attached to their bodies was extracted for palynological identification and to estimate interaction networks. The euglossine community consisted of at least 22 species including Eg. maculilabris, Eg. orellana, Eg. championi and Eg. ignita. The male bees were associated with 84 plants but depended on a small group of them (Peperomia spp. and Anthurium spp, as well as species of Solanaceae, Ericaceae and Malpighiaceae) which were widely distributed across the altitudinal gradient, and were available through the year. The resulting interaction networks revealed a typical nested pattern usually found in plant-pollinator interactions, with several rare bee and plant species interaction with a small group of generalist bees and plant species. Albeit, we found variation within networks related to species composition. Such variation may be a consequence of specific differences in plant flowering phenology.